The collected writings of John Maynard Keynes, Volume 9, Essays in persuasion - Keynes, John Maynard 1883-1946 (The collected writings of John Maynard Keynes, 2013)
Most of the essays in this book were first collected together in October 1931, immediately after Britain had left the gold standard. They reflected Keynes's attempts over the previous dozen years to influence public opinion and policy over the Treaty of Versailles, over which he had resigned from the Treasury in June 1919, reparations and inter-allied war debts, stabilisation policy, the gold standard and the shape of liberal politics in Britain. In 1972 the essays were reprinted with the full texts of the pamphlets – Can Lloyd George Do It?, The Economic Consequences of Mr Churchill, A Short View of Russia and The End of Laissez Faire. At that time, the full texts of his two post-1931 pamphlets – The Means to Prosperity and How to Pay for the War – were added. The book contains examples of Keynes's finest writing on economic policy and politics. This edition includes an introduction by Donald Moggridge